Aboriginal youth and the criminal justice system : the injustice of justice? / Fay Gale, Rebecca Bailey-Harris, Joy Wundersitz. - Gale, Fay; Bailey-Harris, Rebecca J.; Wundersitz, Joy (Cambridge University Press, 1990)
This book is a 1990 account of the ways in which young Aborigines were at a disadvantage before laws and legislation had been introduced, intended to improve their position. Aboriginal Youth and the Criminal Justice System focuses on South Australia, where detailed statistics are available, in a sophisticated analysis of the exact nature of the discrimination experienced by young Aborigines. Fay Gale, Rebecca Bailey-Harris and Joy Wundersitz examine the criminal justice system in operation; from the initial intervention by a police officer, through the process of screening and assessment to the final outcome - which all too often is a criminal record. The research clearly shows that at every point where discretion was exercised within this system, Aboriginal youths received the harsher option. Thus disadvantage is heaped on disadvantage until young Aboriginals were imprisoned at 23 times the rate of other young Australians. Even for those who escaped detention, participation in the criminal justice system was often such an ordeal that it became a form of punishment in itself. Discretion, though preferable to inflexible rules could operate against a group whose lifestyle and values differed from mainstream society.